Cognitive modeling of dilution effects in visual search - Schizas, Christos N.; Neokleous, Kleanthis C.; Avraamides, Marios N.; Neocleous, Costas (My University, 2012)
A biologically plausible neural network model of selective attention has been implemented to account for discrepant findings on the source of distractor interference in visual search tasks. The model successfully simulated the findings from an experiment by Benoni and Tsal (2010) documenting the effects of dilution on distractor interference. In conjunction with previous implementations of the model, we have been able to offer a unifying account that settles the controversy between the Perceptual Load and the Dilution theories of selective attention. 2012 Springer-Verlag.
Keywords: Biologically plausible neural networks; Cognitive modeling; Computational modeling; Dilution effect; Perceptual load theory; Selective attention; Spiking neural networks; Visual search; Computer simulation; Data processing; Neural networks; Dilution